The Role of the MUI Infokom Commission in Incorporating Religious Moderation Through Social Media to Build Harmonization of Religious Life - Syarifatunn Nisa; Asep Gunawan; Nabilah Sobriyanti (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This research examines the role of the MUI Infocom Commission in promoting religious moderation through social media in order to create harmonization of religious life. By involving literature as a research method, the research focus is focused on the role of MUI Infocom in disseminating information related to religious moderation. The results show that the MUI Infocom Commission has a strategic role in managing moderation-based content on social media. In an era where the internet and social media have a big influence, this research details how Infokom MUI contributes to shaping understanding of religious moderation and creating harmony amidst religious diversity in Indonesia. Through this approach, it is hoped that this research can contribute to understanding the important role of the MUI Infocom Commission in building harmonization of religious life through social media. PThe importance of moderated content on social media is actually to achieve a humanist Islam and the important role of MUI infocom in disseminating information about MUI's work and activities to the wider community, packaging it in peaceful content in order to form a moderate Islam by packaging each content as interesting and creative. Meanwhile, the MUI's task is as khodimul ummah (serving the ummah), protecting the ummah from various possible hoax information, as well as shodiqul lawah (government partner) in socializing and educating the public with constructive information and communication.